Anti-theft safety paper containing amorphous fibers and method for preparing amorphous fibers

The low coercive amorphous fibers prepared and implanted in paper through the Taylor spinning method solve the problems of low detection rate of anti-theft paper and electromagnetic pollution, and achieve information security protection with high accuracy and low false alarm rates.

CN119194905APending Publication Date: 2024-12-27JIANGSU JICUI ANTAI CHUANGMING ADVANCED ENERGY MATERIALS RES INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310767900.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing anti-theft paper detection rate is low and the detection device will cause electromagnetic pollution, affecting the health of the population, especially pregnant women, children and the elderly.

Method used

Taylor spinning method is used to prepare amorphous fibers with a diameter of 20-50 microns and a length of 3-15 mm. After removing the glass cladding layer, the amorphous fiber content is greater than or equal to 50m/m2, and has low coercive force. and high detection performance.

Benefits of technology

It significantly improves the detection accuracy of anti-theft paper, reduces electromagnetic pollution, and the false alarm rate is less than one thousandth, ensuring information security.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194905A_ABST
    Figure CN119194905A_ABST
Patent Text Reader

Abstract

The invention relates to anti-theft safety paper containing amorphous fibers with low coercive force and high detection performance. The paper comprises a paper body and amorphous fibers implanted into the paper body, wherein the amorphous fibers have a large Barkhausen effect. The manufacturing method of the amorphous fiber comprises the following steps: firstly, preparing an amorphous composite filament by a Taylor method, and crushing a glass coating layer by a rolling roller to obtain an amorphous core; and shearing the amorphous core to obtain the low-coercivity amorphous fiber. The amorphous fiber is not provided with a coating layer and has low coercive force. The anti-theft safety paper containing the amorphous fibers has high detectability and can be easily detected by a detection device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material technology, and specifically relates to an anti-theft safety paper containing amorphous fibers, and a method for preparing the amorphous fibers used in the anti-theft safety paper. Background Art

[0002] Information security is an issue that any country must pay great attention to. It is a national security strategy that cannot be ignored. With the rapid development of my country's economy, more and more companies and institutions are facing the risk of losing paper documents and leaking their business secrets. Not only that, hostile forces or illegal organizations use various means to steal secret information in politics, military, economy, science and technology, etc. How the government, military and companies can ensure information security has become an urgent problem to be solved. Nowadays, there are many confidential or important paper documents that are not allowed to be taken out of the confidential area without authorization. This requires the protection of these confidential papers. It is required that when someone tries to illegally carry confidential papers out of the confidential area, special detection means can be used to sense and alarm.

[0003] The existing technology uses amorphous composite fibers to protect confidential paper. Amorphous composite fibers have a large Barkhausen effect, that is, the domain wall of the material undergoes a jumping irreversible displacement process during the magnetization process, which can be detected by instruments. When the amorphous composite fiber is placed in an alternating magnetic field, when the magnetic field reaches the switching field of the material, the magnetic domain of the material changes instantly, and the instrument can sense a unique electromagnetic signal. In actual applications, the detection equipment is placed at the exit of the confidential area. When someone enters the detection area with paper implanted with amorphous composite fibers, the detection instrument will detect an electromagnetic signal and then alarm.

[0004] The current anti-theft paper widely used in the market generally has the problem of low detection rate and inability to effectively alarm. This defect directly affects the safety of paper, and improving the detection rate is an urgent problem to be solved. In addition, the current detection device will release a large amount of electromagnetic pollution when detecting anti-theft security paper, which will cause harm to the public, especially pregnant women, children, the elderly, etc.

[0005] The amorphous composite wire made by the Taylor method, which contains a glass coating and an amorphous core, has a high coercivity and requires a high-intensity magnetic field to be accurately detected by the detection device, which is easy to cause electromagnetic pollution and has a low detection rate, and is prone to missed detection. When using low-coercivity amorphous fibers, the electromagnetic field intensity is small, there is almost no electromagnetic pollution, and the detection accuracy is extremely high.

[0006] Therefore, it is necessary to invent an anti-theft security paper containing amorphous fibers with low coercivity and high detection performance. Summary of the invention

[0007] The present invention uses the Taylor spinning method to produce amorphous fibers with a diameter of 20-50 microns and a length of 3-15 mm, which have a large Barkhausen effect. After the glass coating produced by the Taylor spinning method is removed by rolling, the amorphous fibers of the aforementioned length and diameter are implanted into paper (the content of amorphous fibers is greater than or equal to 50 m / m 2 ), a theft-proof security paper containing amorphous fibers with low coercivity and high detection performance was obtained.

[0008] Therefore, the present invention includes the following embodiments:

[0009] Embodiment 1. A theft-proof safety paper containing amorphous fibers, comprising a paper body formed of plant fibers and amorphous fibers embedded in the paper body,

[0010] The amorphous fiber has a large Barkhausen effect; the diameter of the amorphous fiber is 20-50 microns; the length of the amorphous fiber is 3-15 mm or 4 to 9 mm; the coercive force of the amorphous fiber is 0.01-0.8 A / m; the amorphous fiber does not have a coating layer; the content of the amorphous fiber is greater than or equal to 50 m / m2.

[0011] Embodiment 2. The anti-theft safety paper according to embodiment 1 is characterized in that the coercive force of the amorphous fibers is 0.01-0.3 A / m.

[0012] Embodiment 3. The anti-theft safety paper according to embodiment 1 is characterized in that the content of the amorphous fibers in the anti-theft safety paper is greater than or equal to 100 m / m2.

[0013] Embodiment 4. The anti-theft safety paper according to embodiment 1 is characterized in that the anti-theft safety paper is prepared by directly implanting the amorphous fibers into the paper body.

[0014] Embodiment 5. The anti-theft safety paper according to embodiment 1 is characterized in that the diameter of the amorphous fibers is 30-40 microns; the length of the amorphous fibers is 3-8 mm.

[0015] Embodiment 6. The anti-theft security paper according to embodiment 1 is characterized in that the orientation of the amorphous fibers in the paper body is randomly oriented.

[0016] Embodiment 7. The anti-theft safety paper according to embodiment 1 is characterized in that the amorphous fiber is a cobalt-based amorphous soft magnetic material, which contains:

[0017] a) one or more elements selected from Co, Fe, Mn and Ni;

[0018] b) one or more elements selected from Si, B, and C; and

[0019] c) Optional rare earth or transition group metals.

[0020] Embodiment 8. The anti-theft safety paper according to embodiment 1 is characterized in that the amorphous fiber is a cobalt-based amorphous soft magnetic material, which contains:

[0021] 1-15 wt% Fe;

[0022] 2-12 wt% Si;

[0023] One or more selected from B, Nb, Cu, Mn, Mo, Ni, Cr and Al in a total amount of 2-25 wt.%; and

[0024] The balance of Co.

[0025] Embodiment 9. The anti-theft safety paper according to embodiment 6 or 7, characterized in that the amorphous fiber is prepared by the following method:

[0026] An amorphous composite wire containing a glass cladding and an amorphous core is prepared by the Taylor method, wherein the coercive force of the amorphous composite wire is greater than 5A / m, and the diameter of the amorphous core is 20-50 microns. The amorphous composite wire is continuously passed through a rolling roller in a cooling state, and the rolling pressure of the rolling roller causes the glass cladding to break and separate from the amorphous core. The separated amorphous core is cut into a length of 3-15mm or 4 to 9mm to obtain the amorphous fiber.

[0027] Embodiment 10. A method for preparing amorphous fibers, characterized in that it comprises the following steps:

[0028] Step 1: Insert the master alloy rod into the bottom of the glass tube;

[0029] Step 2: Using induction heating to melt the master alloy rod at the bottom of the glass tube to form a molten master alloy, and the molten master alloy softens the bottom of the glass tube;

[0030] Step 3: Pull out the microwire from the bottom of the softened glass tube to obtain an amorphous composite wire prototype containing a glass coating layer and an amorphous core;

[0031] Step 4: rapidly cooling the amorphous composite wire to obtain a cooled amorphous composite wire or making the temperature of the amorphous composite wire lower than the induction heating temperature of step 2;

[0032] Step 5: allowing the amorphous composite wire to continuously pass through a roller gap formed by a rolling roller in a cooled state or allowing the amorphous composite wire to continuously pass through a roller gap formed by a rolling roller in a heated state, wherein the width of the roller gap is greater than the diameter of the amorphous core and smaller than the diameter of the amorphous composite wire, so that the rolling force causes the glass cladding layer to break and separate from the amorphous core;

[0033] Step 6: Cut the separated amorphous core into pieces with a length of 3-15 mm or 4 to 9 mm to obtain the amorphous fiber;

[0034] The master alloy rod contains:

[0035] 1-15 wt% Fe;

[0036] 2-12 wt% Si;

[0037] One or more selected from B, Nb, Cu, Mn, Mo, Ni, Cr and Al in a total amount of 2-25 wt.%; and

[0038] The balance of Co;

[0039] The amorphous fiber has a large Barkhausen effect; the diameter of the amorphous fiber is 20-50 microns; the length of the amorphous fiber is 3-15 mm or 4 to 9 mm; the coercive force of the amorphous fiber is 0.01-0.8 A / m; and the amorphous fiber has no coating layer.

[0040] The glass-coated spinning method used in this application is suitable for batch production of amorphous fibers at low cost. The master alloy rod contains metal elements such as Co. A glass coating layer is generated during the preparation process, which generates a large internal stress and increases the coercive force. During the detection, the detection device uses the hysteresis loop through the large Barkhausen effect to detect, which requires a large magnetic field strength and will generate a large electromagnetic pollution. The glass coating layer is broken or peeled off by rolling, so that the generated amorphous core does not have a glass coating layer, which greatly reduces the coercive force, makes the paper easy to detect and helps reduce electromagnetic pollution.

[0041] The amorphous fibers are made into 20-50 microns in diameter and 3-15 mm or 4 to 9 mm in length, similar to pulp fibers, and are easier to implant in papermaking. The coercive force is 0.01-0.8 A / m, making it easy to detect by the detection device. The amorphous fiber content is greater than or equal to 50 m / m 2 This greatly improves the detection rate in actual applications, and the false alarm rate is less than one thousandth. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings of the embodiments will be briefly introduced below. Obviously, the drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.

[0043] Figure 1 : Schematic diagram of the method for preparing an amorphous core

[0044] Figure 2 :Schematic diagram of the Taylor method for preparing glass-coated amorphous composite wire

[0045] Figure 3 : Schematic diagram of the cross section of amorphous composite wire

[0046] Figure 4 : Schematic diagram of rolling roller rolling

[0047] Figure 5 : Large Barkhausen effect curve of amorphous fiber.

[0048] Figure 6 : Schematic diagram of anti-theft security paper containing disordered full-page distributed amorphous fibers.

[0049] In the figure: 11-feeding area, 12-glass tube, 13-master alloy rod, 14-heating area, 15-high frequency induction furnace, 16-cooling area, 17-cooling liquid, 18-amorphous composite wire, 19-wire collection roller, 20-rolling roller, 21-glass coating, 22-amorphous core, 23-amorphous fiber, 24-anti-theft safety paper. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] definition:

[0052] In the present application, the term "large Barkhausen effect" refers to a property of amorphous ribbons or fibers, that is, the domain wall of the material undergoes a jump-like movement or reversal during the magnetization process, and this process can be detected by an instrument. In actual detection, the amorphous fiber is placed in an alternating magnetic field. When the magnetic field reaches the switching field of the material, the magnetic domain of the material changes instantaneously, and the detection instrument can sense a unique electromagnetic signal. In some embodiments, the induced electromagnetic signal is a pulse signal or a high-order harmonic. The amorphous fiber in the present invention has a large Barkhausen effect, such as Figure 3As shown, under the stimulation of the alternating magnetic field, when a switching magnetic field value is reached, the magnetic induction intensity will jump, thereby inducing an electromagnetic signal, such as a pulse signal or high-order harmonics. When the detection instrument detects the electromagnetic signal generated by the amorphous fiber, it will alarm.

[0053] In this application, the term "Taylor spinning process" refers to a method of spinning by the following steps:

[0054] In this application, the term "Taylor spinning process" refers to a method of spinning by the following steps:

[0055] 1. First, provide a master alloy rod with the required composition and select a glass tube that matches it. The difference between the melting point of the master alloy and the softening temperature of the glass tube is higher than 50°C and lower than 500°C;

[0056] 2. Insert the master alloy rod into the bottom of the glass tube;

[0057] 3. Use high frequency induction furnace to melt the bottom of the master alloy rod;

[0058] 4. Use the molten master alloy to soften the glass tube;

[0059] 5. Pull out the wire by pulling;

[0060] 6. The mother alloy in a molten state is cooled by rapid solidification to form an amorphous composite wire.

[0061] The method may further include the following steps:

[0062] 7. Winding the amorphous composite wire on a wire-receiving roller, the winding speed of the amorphous composite wire keeps the linear speed constant;

[0063] 8. Maintain the stability of the drawing process by adjusting parameters such as feeding speed and temperature.

[0064] Realize the continuous preparation of silk.

[0065] In this application, the term "amorphous fiber" has the meaning commonly understood by those skilled in the art. Generally speaking, it refers to an alloy fiber containing multiple alloy elements, such as Co, Fe, Mn, Ni, Si, B, C and transition metal elements.

[0066] The present invention provides an anti-theft safety paper containing amorphous fibers, which comprises a paper body formed of plant fibers and amorphous fibers implanted in the paper body.

[0067] The amorphous fiber has a large Barkhausen effect; the diameter of the amorphous fiber is 20-50 microns; the length of the amorphous fiber is 3-15 mm or 4 to 9 mm; the coercive force of the amorphous fiber is 0.01-0.8 A / m; the amorphous fiber has no coating layer; the content of the amorphous fiber is greater than or equal to 50 m / m 2 .

[0068] During the detection, the detection device uses the hysteresis loop through the large Barkhausen effect, which requires a large magnetic field strength and will generate a large amount of electromagnetic pollution. The glass coating is broken or peeled off by rolling, so that the generated amorphous core does not have a glass coating, which greatly reduces the coercive force, makes the paper easy to detect and helps reduce electromagnetic pollution.

[0069] The inventors of the present invention have found that amorphous fibers are made into 20-50 microns in diameter and 3-15 mm or 4 to 9 mm in length, which makes them similar to pulp fibers and easier to implant in papermaking. The coercive force is 0.01-0.8 A / m and the amorphous fiber content is greater than or equal to 50 m / m. 2 This makes it easy for the detection device to detect, greatly improving the detection rate in actual applications, and the false alarm rate is less than 1‰.

[0070] In one embodiment, the coercivity of the amorphous fiber is 0.01-0.3 A / m. When the coercivity of the amorphous fiber is 0.01-0.3 A / m, the amorphous fiber with a large Barkhausen effect can be detected by a detection device with a smaller electromagnetic field strength, thereby reducing electromagnetic pollution and improving the detection rate.

[0071] In one embodiment, the content of the amorphous fibers in the anti-theft safety paper is greater than or equal to 100 m / m 2 In this embodiment, the content of amorphous fibers in each A4 paper is 6 to 7 m. When the content of amorphous fibers is higher than 100 m / m 2 When the content of amorphous fibers in each A4 paper is 6 to 7 meters, the detection equipment currently on the market can detect it with extremely high accuracy, increasing the content of amorphous fibers in anti-theft security paper to more than 100m / m 2 , the detection device can effectively reduce the false alarm rate.

[0072] In one embodiment, the anti-theft safety paper is prepared by directly implanting the amorphous fibers into the paper body. The implantation method can ensure that the fibers are not exposed, and the thickness and size of the anti-theft safety paper are consistent with ordinary paper, and can be printed and copied normally. It has a higher hardness than ordinary paper, and its durability is greatly increased.

[0073] In one embodiment, the diameter of the amorphous fiber is 30-40 microns; the length of the amorphous fiber is 3-8 mm. When the diameter of the amorphous fiber is 30-40 microns and the length is 3-8 mm, it is most suitable for the papermaking process. When the amorphous fiber is too long, it is easy to expose the paper, and the production cost increases. In ordinary paper, the difference between amorphous fiber and pulp fiber is too large, which often has an adverse effect on the papermaking process. If it is too short, it affects the detection performance, resulting in a reduced detection rate.

[0074] In one embodiment, the amorphous fibers are randomly oriented in the paper body.

[0075] The random orientation of amorphous fibers does not affect the detection performance, which can greatly save production time and cost. For the anti-theft safety paper of the present invention, the distribution range of the amorphous fibers in the paper is not limited. In a specific embodiment, the amorphous fibers can be distributed in the anti-theft safety paper in the form of full-page distribution, positioning distribution or a combination thereof. Full-page distribution means that the distribution range of amorphous fibers is throughout the entire paper. Positioning distribution means that the distribution range of amorphous fibers is within a fixed range of the paper, such as only at the edge of the paper, or a corner.

[0076] In one embodiment, the amorphous fiber is a cobalt-based amorphous soft magnetic material, which contains:

[0077] a) one or more elements selected from Co, Fe, Mn and Ni;

[0078] b) one or more elements selected from Si, B, and C; and

[0079] c) Optional rare earth or transition group metals.

[0080] In the amorphous fiber composed of this composition, component a) is a component with ferromagnetic material, and component b) is a non-metallic alloy element. Component c) is optionally added, and different ratios of the added components may cause the switching field position of the material to produce a large Barkhausen effect to shift. The material generated by this alloy composition method is an amorphous soft magnetic material, which is easy to magnetize and demagnetize, has the characteristics of low coercive force and high magnetic flux, and is a high-quality material for making amorphous fibers.

[0081] In one embodiment, the amorphous fiber is a cobalt-based amorphous soft magnetic material, which contains:

[0082] 1-15 wt% Fe;

[0083] 2-12 wt% Si;

[0084] One or more selected from B, Nb, Cu, Mn, Mo, Ni, Cr and Al in a total amount of 2-25 wt.%; and

[0085] The balance of Co.

[0086] Among the amorphous fibers composed of the above components, the one preferred in the present invention is that the material source is wide, easy to obtain, the processing method is simple and easy to prepare, and it also has the characteristics of low coercive force and high magnetic flux, and is a more preferred material for making amorphous fibers.

[0087] In one embodiment, the amorphous fiber is prepared by the following method:

[0088] An amorphous composite wire containing a glass cladding and an amorphous core is prepared by the Taylor method, wherein the coercive force of the amorphous composite wire is greater than 5A / m, and the diameter of the amorphous core is 20-50 microns. The amorphous composite wire is continuously passed through a rolling roller in a cooling state, and the rolling pressure of the rolling roller causes the glass cladding to break and separate from the amorphous core. The separated amorphous core is cut into a length of 3-15mm or 4 to 9mm to obtain the amorphous fiber.

[0089] Amorphous composite wire with glass coating has a large coercive force, which is not conducive to detection and will also produce a large amount of electromagnetic pollution. Therefore, after the glass coating wire is prepared and cooled, the glass coating layer is squeezed and crushed by a rolling roller, so that the glass coating layer naturally falls off from the surface of the amorphous composite wire. Then, the amorphous core is cut into a certain length by shearing to obtain amorphous fiber that can be used. The amorphous fiber prepared in this way has a low coercive force and a small diameter, and is easy to detect after being implanted into paper.

[0090] In one embodiment, the preparation of amorphous fibers is characterized by comprising the following steps:

[0091] Step 1: Insert the master alloy rod into the bottom of the glass tube;

[0092] Step 2: Using induction heating to melt the master alloy rod at the bottom of the glass tube to form a molten master alloy, and the molten master alloy softens the bottom of the glass tube;

[0093] Step 3: Pull out the microwire from the bottom of the softened glass tube to obtain an amorphous composite wire prototype containing a glass coating layer and an amorphous core;

[0094] Step 4: rapidly cooling the amorphous composite wire to obtain a cooled amorphous composite wire or making the temperature of the amorphous composite wire lower than the induction heating temperature of step 2;

[0095] Step 5: allowing the amorphous composite wire to continuously pass through a roller gap formed by a rolling roller in a cooled state or allowing the amorphous composite wire to continuously pass through a roller gap formed by a rolling roller in a heated state, wherein the width of the roller gap is greater than the diameter of the amorphous core and smaller than the diameter of the amorphous composite wire, so that the rolling force causes the glass cladding layer to break and separate from the amorphous core;

[0096] Step 6: Cut the separated amorphous core into pieces with a length of 3-15 mm or 4 to 9 mm to obtain the amorphous fiber;

[0097] The master alloy rod contains:

[0098] 1-15 wt% Fe;

[0099] 2-12 wt% Si;

[0100] One or more selected from B, Nb, Cu, Mn, Mo, Ni, Cr and Al in a total amount of 2-25 wt.%; and

[0101] The balance of Co;

[0102] The amorphous fiber has a large Barkhausen effect; the diameter of the amorphous fiber is 20-50 microns; the length of the amorphous fiber is 3-15 mm or 4 to 9 mm; the coercive force of the amorphous fiber is 0.01-0.8 A / m; and the amorphous fiber has no coating layer.

[0103] The Taylor spinning method for preparing the amorphous fiber of the present invention has many advantages. First, the Taylor spinning method can prepare an amorphous composite filament with a diameter of 20-50 microns, which usually has a glass coating layer to form a glass-coated amorphous composite filament. The Taylor spinning method can prepare the amorphous composite filament in a continuous and stable manner, and the prepared amorphous composite filament is easy to collect and easy to cut to form an amorphous fiber with a desired length.

[0104] In order to better remove the glass coating, multiple groups of rolling rollers can be set, and the size of the roller gap generated by them decreases. When the amorphous composite wire passes through one by one, the glass coating that was not completely removed in the previous rolling process is rolled and peeled off again. The rolling roller can have a self-cooling function to quickly cool the amorphous composite wire. Cooling and rolling are carried out simultaneously, which can save the previous cooling step and make the entire production process more efficient.

[0105] After the amorphous fibers are prepared, the amorphous fibers can be mixed into papermaking raw materials such as pulp during papermaking to prepare the anti-theft safety paper of the present invention. In this way, the anti-theft safety paper with disorderly arranged amorphous fibers can be prepared.

[0106] After the amorphous fibers are prepared, the amorphous fibers can be mixed into papermaking raw materials such as pulp during papermaking to prepare the anti-theft safety paper of the present invention. In this way, the anti-theft safety paper with disorderly arranged amorphous fibers can be prepared.

[0107] Example

[0108] The raw materials used in the embodiments of the present invention are all conventional and can be purchased from the market or prepared in the laboratory by conventional methods.

[0109] The detection device used in the embodiment of the present invention is an electromagnetic (EM) tag detection device, such as an electromagnetic tag detection door produced by Sensortronics.

[0110] The principle of the detection can be described as follows:

[0111] The detection device contains a signal transmitter and a signal receiver. The signal transmitter generates an excitation magnetic field area by applying an alternating current or alternating voltage in the induction coil. The excitation magnetic field is an alternating magnetic field. The signal receiver is an induction coil. When the amorphous fiber enters the excitation magnetic field area, due to its large Barkhausen effect, under the excitation of the alternating magnetic field, its internal magnetic domain structure will change rapidly, and an electromagnetic pulse signal or high-order harmonics will be induced in the induction coil in the signal receiver. When the signal receiver detects an electromagnetic pulse signal or high-order harmonics, it means that the target detection object appears in the detection area.

[0112] Example 1

[0113] The specific preparation method of the anti-theft security paper containing amorphous fibers with low coercivity and high detection performance is as follows:

[0114] like Figure 1 As shown, the method for making the amorphous fibers included in the anti-theft safety paper 1 is as follows:

[0115] First, a Co-based master alloy rod 13 is provided, the master alloy rod 13 has a melting point of 970°C, a diameter of 7mm, and a composition of Co71.8Fe4.9Nb0.8Si7.5B15, that is, a Co content of 71.8wt%, a Fe content of 4.9wt%, a Nb content of 0.8wt%, a Si content of 7.5wt%, and a B content of 15wt%. A glass tube 12 with a softening temperature of 780°C, an outer diameter of 12mm, and a wall thickness of 1mm is selected.

[0116] Insert the master alloy rod 13 into the bottom of the glass tube 12;

[0117] A high frequency induction furnace is used to melt the master alloy rod 13 and heat it to 1200°C;

[0118] Softening the glass tube 12 using the molten master alloy rod 13;

[0119] The wire is pulled out by drawing;

[0120] The mother alloy in a molten state is cooled by the cooling zone 16 and the cooling liquid 17 to form an amorphous composite wire 18. The structure of the amorphous composite wire 18 is as follows: Figure 3As shown, its diameter is 35 microns and the glass coating is 15 microns;

[0121] like Figure 4 As shown, the roller gap formed by the two rolling rollers 20 is 38 microns. The amorphous composite wire passes through the roller gap and is rolled to peel off the glass coating layer 21 to form an amorphous core 22.

[0122] The amorphous core 22 is wound on the wire-receiving roller 19 at a wire-receiving speed of 30 m / min, ensuring that the diameter of the amorphous core 22 is 35 mm;

[0123] By adjusting parameters such as feeding speed and temperature, the drawing process is kept stable and continuous preparation of the amorphous core 22 is achieved.

[0124] The obtained continuous amorphous core 22 is continuously cut into amorphous fibers 23 of 4 mm.

[0125] The coercive force of amorphous fiber is measured to be 0.1A / m. Figure 5 It is shown that it has a large Barkhausen effect.

[0126] Mix the pulp with an appropriate amount of amorphous fibers to ensure that the prepared paper can obtain an amorphous fiber content of 75m / m 2 of paper.

[0127] The pulp is made into A4 anti-theft safety paper of size, and the anti-theft safety paper is as follows Figure 6 As shown, the instrument detection area is repeatedly entered, and the number of successful detection alarms is 1000 times, with a detection rate of 100%.

[0128] Comparative Example 2

[0129] like Figure 2 As shown, a specific preparation method of an amorphous fiber with a glass coating layer prepared by Taylor spinning is as follows:

[0130] First, a Co-based master alloy rod 13 is provided, the master alloy rod 13 has a melting point of 970°C, a diameter of 7mm, and a composition of Co71.8Fe4.9Nb0.8Si7.5B15, that is, a Co content of 71.8wt%, a Fe content of 4.9wt%, a Nb content of 0.8wt%, a Si content of 7.5wt%, and a B content of 15wt%. A glass tube 12 with a softening temperature of 780°C, an outer diameter of 12mm, and a wall thickness of 1mm is selected.

[0131] Insert the master alloy rod 13 into the bottom of the glass tube 12;

[0132] A high frequency induction furnace is used to melt the master alloy rod 13 and heat it to 1200°C;

[0133] Softening the glass tube 12 using the molten master alloy rod 13;

[0134] The wire is pulled out by drawing;

[0135] The master alloy in a molten state is cooled by passing through a cooling zone 16 and a cooling liquid 17 to form an amorphous composite wire having a diameter of 35 microns and a glass coating of 15 microns;

[0136] The amorphous composite wire 18 is wound on the wire-receiving roller 19 at a wire-receiving speed of 30 m / min, ensuring that the diameter of the amorphous core 22 is 35 mm;

[0137] By adjusting parameters such as feeding speed and temperature, the drawing process is kept stable and continuous preparation of the amorphous composite wire 18 is achieved.

[0138] The obtained continuous amorphous composite filament 18 is continuously cut into 4 mm amorphous fibers with a glass coating.

[0139] The coercive force of the amorphous fiber with a glass coating layer was measured to be 5.2 A / m.

[0140] The pulp is mixed with an appropriate amount of amorphous fibers with a glass coating to ensure that the prepared paper can obtain an amorphous fiber content of 75m / m 2 of paper.

[0141] The pulp was made into A4 anti-theft security paper of size and repeatedly entered the instrument detection area. The number of successful alarms in 1000 detections was 985 times, and the detection rate was 98.5%.

[0142] Example 3

[0143] The specific preparation method of the anti-theft security paper containing amorphous fibers with low coercivity and high detection performance is as follows:

[0144] The method for preparing the amorphous fibers contained in the anti-theft safety paper 1 is as follows:

[0145] First, a Co-based master alloy rod 13 is provided, the master alloy rod 13 has a melting point of 970°C, a diameter of 7mm, and a composition of Co71.8Fe4.9Nb0.8Si7.5B15, that is, a Co content of 71.8wt%, a Fe content of 4.9wt%, a Nb content of 0.8wt%, a Si content of 7.5wt%, and a B content of 15wt%. A glass tube 12 with a softening temperature of 780°C, an outer diameter of 12mm, and a wall thickness of 1mm is selected.

[0146] Insert the master alloy rod 13 into the bottom of the glass tube 12;

[0147] A high frequency induction furnace is used to melt the master alloy rod 13 and heat it to 1200°C;

[0148] Softening the glass tube 12 using the molten master alloy rod 13;

[0149] The wire is pulled out by drawing;

[0150] The structure of the amorphous composite wire 18 in the heated state is as follows Figure 3 As shown, its diameter is 35 microns and the glass coating is 5 microns;

[0151] like Figure 4 As shown, in this embodiment, three groups of rolling rollers 20 are arranged, and the first group of rolling rollers 20 has a self-cooling function, which can cool down the amorphous composite wire 18. The roller gap 21 formed by the first group of rolling rollers 20 is 42 microns, the roller gap 21 formed by the second group of two rolling rollers 20 is 38 microns, and the roller gap 21 formed by the third group of two rolling rollers 20 is 35 microns. The amorphous composite wire passes through the roller gap and is rolled to peel off the glass coating layer 21 to form an amorphous core 22.

[0152] The amorphous core 22 is wound on the wire-receiving roller 19 at a wire-receiving speed of 30 m / min, ensuring that the diameter of the amorphous core 22 is 35 mm;

[0153] By adjusting parameters such as feeding speed and temperature, the drawing process is kept stable and continuous preparation of the amorphous core 22 is achieved.

[0154] The obtained continuous amorphous core 22 is continuously cut into amorphous fibers 23 of 4 mm.

[0155] The coercive force of amorphous fiber is measured to be 0.1A / m. Figure 5 It is shown that it has a large Barkhausen effect.

[0156] Mix the pulp with an appropriate amount of amorphous fibers to ensure that the prepared paper can obtain an amorphous fiber content of 75m / m 2 of paper.

[0157] The pulp is made into A4 anti-theft safety paper of size, and the anti-theft safety paper is as follows Figure 6 As shown, the instrument detection area is repeatedly entered, and the number of successful detection alarms is 1000 times, with a detection rate of 100%.

[0158] This embodiment is provided with three groups of rolling rollers, and the first group has a self-cooling function. When the amorphous composite wire with a heating temperature enters the rolling rollers, the rolling rollers can cool it, thus eliminating the cooling step and greatly saving the time of the production process.

[0159] In addition, the three groups of rolling rollers are set with different roller gaps, the first group has the largest roller gap, and each subsequent group of rolling roller gaps decreases in sequence. This allows the glass coating to be rolled by multiple groups of rolling rollers for multiple peelings. If the glass coating is not completely removed in the first peeling, the subsequent rolling process will damage the glass coating again, and the overall peeling effect of the glass coating is better.

[0160] Example 4

[0161] Papers with different amorphous fiber contents were prepared by directly implanting the amorphous fibers prepared in Example 1 into paper, wherein the total length distribution of the amorphous fibers in the paper was 1 m / A4 paper, 1.5 m / A4 paper, 3 m / A4 paper, and 4.5 m / A4 paper, respectively. The prepared paper containing amorphous fibers was tested, and the results were as follows:

[0162]

[0163]

[0164] From the above results, it can be seen that the amorphous fiber prepared in Example 1 has a large Barkhausen effect. When the length of the amorphous fiber is less than or equal to 1 mm, the detection rate of the instrument for such anti-theft safety paper is less than 62%, but when the length of the amorphous fiber is greater than 3 mm, the detection rate of the instrument for anti-theft safety paper is greater than 97.6%, especially when the total length of the amorphous fiber in the A4 paper is greater than 6 m, the detection rate reaches more than 98.9%.

[0165] The above description is merely an exemplary embodiment of the present invention and is not intended to limit the protection scope of the present invention. The protection scope of the present invention is determined by the appended claims.

Claims

1. An anti-theft safety paper containing amorphous fibers, comprising a paper body formed of plant fibers and amorphous fibers embedded in the paper body, The amorphous fiber has a large Barkhausen effect; the diameter of the amorphous fiber is 20-50 microns; the length of the amorphous fiber is 3-15 mm or 4 to 9 mm; the coercive force of the amorphous fiber is 0.01-0.8 A / m; the amorphous fiber has no coating layer; the content of the amorphous fiber is greater than or equal to 50 m / m 2 .

2. The anti-theft safety paper according to claim 1, characterized in that: The coercive force of the amorphous fiber is 0.01-0.3 A / m.

3. The anti-theft safety paper according to claim 1, characterized in that: The content of the amorphous fibers in the anti-theft safety paper is greater than or equal to 100 m / m 2 .

4. The anti-theft safety paper according to claim 1, characterized in that: The anti-theft safety paper is prepared by directly implanting the amorphous fibers into the paper body.

5. The anti-theft safety paper according to claim 1, characterized in that: The diameter of the amorphous fiber is 30-40 microns; the length of the amorphous fiber is 3-8 mm.

6. The anti-theft safety paper according to claim 1, characterized in that: The orientation of the amorphous fibers in the paper body is random.

7. The anti-theft safety paper according to claim 1, characterized in that: The amorphous fiber is a cobalt-based amorphous soft magnetic material, which contains: a) one or more elements selected from Co, Fe, Mn and Ni; b) one or more elements selected from Si, B, and C; and c) Optional rare earth or transition group metals.

8. The anti-theft safety paper according to claim 1, characterized in that: The amorphous fiber is a cobalt-based amorphous soft magnetic material, which contains: 1-15 wt% Fe; 2-12 wt% Si; One or more selected from B, Nb, Cu, Mn, Mo, Ni, Cr and Al in a total amount of 2-25 wt.%; and The balance of Co.

9. The anti-theft safety paper according to claim 6 or 7, characterized in that: The amorphous fiber is prepared by the following method: An amorphous composite wire containing a glass cladding and an amorphous core is prepared by the Taylor method, wherein the coercive force of the amorphous composite wire is greater than 5A / m, and the diameter of the amorphous core is 20-50 microns. The amorphous composite wire is continuously passed through a rolling roller in a cooling state, and the rolling pressure of the rolling roller causes the glass cladding to break and separate from the amorphous core. The separated amorphous core is cut into a length of 3-15mm or 4 to 9mm to obtain the amorphous fiber.

10. A method for preparing amorphous fibers, characterized in that: The steps include: Step 1: Insert the master alloy rod into the bottom of the glass tube; Step 2: Using induction heating to melt the master alloy rod at the bottom of the glass tube to form a molten master alloy, and the molten master alloy softens the bottom of the glass tube; Step 3: Pull out the microwire from the bottom of the softened glass tube to obtain an amorphous composite wire prototype containing a glass coating layer and an amorphous core; Step 4: rapidly cooling the amorphous composite wire to obtain a cooled amorphous composite wire or making the temperature of the amorphous composite wire lower than the induction heating temperature of step 2; Step 5: allowing the amorphous composite wire to continuously pass through a roller gap formed by a rolling roller in a cooled state or allowing the amorphous composite wire to continuously pass through a roller gap formed by a rolling roller in a heated state, wherein the width of the roller gap is greater than the diameter of the amorphous core and smaller than the diameter of the amorphous composite wire, so that the rolling force causes the glass cladding layer to break and separate from the amorphous core; Step 6: Cut the separated amorphous core into pieces with a length of 3-15 mm or 4 to 9 mm to obtain the amorphous fiber; The master alloy rod contains: 1-15 wt% Fe; 2-12 wt% Si; One or more selected from B, Nb, Cu, Mn, Mo, Ni, Cr and Al in a total amount of 2-25 wt.%; and The balance of Co; The amorphous fiber has a large Barkhausen effect; the diameter of the amorphous fiber is 20-50 microns; the length of the amorphous fiber is 3-15 mm or 4 to 9 mm; the coercive force of the amorphous fiber is 0.01-0.8 A / m; and the amorphous fiber has no coating layer.

Citation Information

Patent Citations

  • Antitheft safety paper

    CN106192549A

  • Recording medium

    CN106257981A

  • Preparation method for glass-coated amorphous microwires

    CN106756640A

  • Preparation method of nanocrystalline magnetic core

    CN114694944A

  • Writing / reading papers for security

    KR1020170005728A